2019
DOI: 10.1002/aenm.201902446
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High‐Voltage and High‐Capacity Aqueous Rechargeable Zinc Ion Battery by Incorporating Two‐Species Redox Reaction

Abstract: safety, and low cost. [1][2][3][4][5] However, the strong electrostatic interaction with host materials originating from divalent chemistry leads to low output voltage, poor reversibility, and especially sluggish kinetics. Various cathode materials have been developed to navigate these challenges. Currently, the most studied cathode active materials are manganesebased [6][7][8][9] and vanadium-based [10][11][12][13] composites. Nonetheless, relative low operating voltage and poor rate performance remains as is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
296
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 410 publications
(317 citation statements)
references
References 54 publications
(147 reference statements)
3
296
0
1
Order By: Relevance
“…As the cycle progresses, by the 10 th cycle, broad redox peaks at 0.7/0.3V and 0.5/1.0-1.6 V appear, completely agreeing with the electrochemical behavior of V 2 CT X MXene in the previous study. [11,[29][30][31] Meanwhile, these features that Figure 3. Characterization of phase and structure transition of V 2 CT X MXene during further cycling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the cycle progresses, by the 10 th cycle, broad redox peaks at 0.7/0.3V and 0.5/1.0-1.6 V appear, completely agreeing with the electrochemical behavior of V 2 CT X MXene in the previous study. [11,[29][30][31] Meanwhile, these features that Figure 3. Characterization of phase and structure transition of V 2 CT X MXene during further cycling.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4g reviews the rate performance of V-based aqueous zinc batteries reported in recent years. [30,37,39,[44][45][46][47][48][49][50][51][52] Our battery based on V 2 AlC cathode offers an excellent rate performance in aspects of both high capacities at a low current density and high current density toleration. In detail, the highest capacity of about 409.7 mAh g −1 with less than 25 mAh g −1 from the carbon cloth and additives can be obtained at 0.5 A g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…M, Schematic of Zn//CoFe(CN) 6 MBs based on PAM electrolyte with and without F77, and, N, corresponding galvanostatic charge/discharge curves. (E‐G,L‐N) Reproduced with permission 30,52,55,59,62 . Copyright 2016, 2018, and 2019, Wiley‐VCH.…”
Section: Zinc Ion Mbsmentioning
confidence: 99%
“…The as‐fabricated MBs offered high specific capacity of 100.2 mAh/cm 3 and superior energy density of 195.39 mWh/cm 3 . To explore the new electrolyte for ensuring the mechanic strength of the MBs, Ma et al 62 invented a new‐type electrolyte (Figure 3M,N) of the PAM with poly (ethylene oxide) 53 ‐poly(propylene oxide) 34 ‐poly(ethylene oxide) (F77), which showed a distinct sol‐gel transition feature from 0°C to room temperature accompanied with the state change from aqueous to gel, contributing to the full utilization of the active material. As a result, this Zn//CoFe(CN) 6 MB delivered admirable long‐term cyclability (93.4% after 2000 cycles).…”
Section: Zinc Ion Mbsmentioning
confidence: 99%
“…These features endow the RZBs with the most competitive candidate for powering flexible and wearable devices. In the past decades, tremendous work was devoted to distinguishing a proper cathode for RZBs, manganese‐based oxides, 11,12 vanadium‐based oxides, 13‐15 cobalt‐base oxides, 16,17 molybdenum‐based materials, 18 prussian blue analogous, 19,20 and other materials. The advances in developing those materials broke many stereotypes, realizing high capacity, high voltage platform, and long lifespan 20‐22 .…”
Section: Introductionmentioning
confidence: 99%